Public Service Motivation as a Mediating Variable of Transformational Leadership: Digital Knowledge Sharing on Performance - Kezia Margareth Ntjalama; Stefanus MS Sadana (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the digital era, transformational leadership and digital knowledge sharing are important factors in driving organizational progress, especially in the education sector. This study aims to analyze how these two factors affect teacher performance, with public service motivation as a mediating variable. The study was conducted with 70 teachers at Junior High School (Sekolah Menengah Pertama/SMP) Negeri 193 Jakarta using a quantitative approach, where data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The findings of the study indicate that transformational leadership, which is inspiring and can encourage innovation, along with digital knowledge sharing that facilitates access to information, significantly contributes to improving teacher performance. In addition, public service motivation is shown to play an important role as a mediator in the relationship between transformational leadership, digital knowledge sharing, and teacher performance. This study provides a practical contribution that can be used by schools or educational institutions in designing effective leadership strategies and utilizing digital technology to improve the quality of teaching and student learning outcomes.of the use of digital technology to improve teacher performance in the education sector.